Pengaruh Motivasi Kerja dan Sistem Kompensasi terhadap Kedisiplinan Kerja Karyawan PT Rajawali Nusindo Cabang Medan - Alfatia, Tasya; Yusrita, Yusrita; Tahir, M. (Universitas Islam Islam Sumatera Utara, 2022)
This research is limited to work motivation and work compensation system, especially about the work targets applied and so is the compensation given by PT. Rajawali Nusindo Medan Branch has not been able to improve work discipline. The formulation of the problem in this study is . Does work motivation and compensation affect the work discipline of employees at PT. Rajawali Nusindo Medan Branch. The purpose of this study is to determine the influence of employee work discipline at PT. Rajawali Nusindo Medan Branch. The population in this study amounted to 57 employees. To determine the sample size that can be representative of the population, this research approach is a quantitative approach. The test method uses SPSS. Based on the results of testing and analysis, it shows that there is a positive and significant influence of work motivation variables on employee performance discipline variables. There is a positive and significant influence of compensation system variables on employee performance discipline variables.